High Psychosocial Work Demands, Decreased Well-Being, and Perceived Well-Being Needs Within Veterinary Academia During the COVID-19 Pandemic - McKee, Hayley; Gohar, Basem; Appleby, Ryan; Nowrouzi-Kia, Behdin; Hagen, Briana N. M.; Jones-Bitton, Andria (Frontiers in Veterinary Science, 2021)
Higher psychosocial work demands in veterinary and academic professions are associated with decreased occupational, physical, and mental well-being. COVID-19 introduced far-reaching challenges that may have increased the psychosocial work demands for these populations, thereby impacting individual- and institutional-level well-being. Our objective was to investigate the psychosocial work demands, health and well-being, and perceived needs of faculty, staff, residents, and interns at the Ontario Veterinary College, in Ontario, Canada, during COVID-19. A total of 157 respondents completed a questionnaire between November 2020 and January 2021, that included the Third Version of the Copenhagen Psychosocial Questionnaire (COPSOQ-III) and open-text questions on perceived needs for well-being. Results showed that COPSOQ-III dimensions of quantitative demands, recognition, sense of community, burnout, stress, and depressive symptoms, were significantly worse in our study population than the Canadian norm. Quantitative and emotional demands, health and well-being (including depressive symptoms, stress, cognitive stress, somatic stress, and burnout), and work-life conflict were also reported to have worsened since the COVID-19 restrictions for most respondents. Females and caregivers had higher odds of experiencing increased work demands, and decreased health and well-being, compared to males and non-caregivers. However, male caregivers experienced worsened supervisor relations, compared to female caregivers. Social capital also worsened for clinical and part-time employees, compared to full-time and non-clinical employees. Respondents identified increased workload support, community-building, recognition of employees’ capacities and personal needs, flexible work schedules, and consistent communication, as strategies to increase well-being during COVID-19 and generally. Overall, our findings suggest that COVID-19 has increased occupational demands, work-life conflicts, and decreased well-being in veterinary academia. Institutional-level interventions are discussed and recommended to aid individual and institutional well-being.